2001
DOI: 10.3136/fstr.7.135
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Extra Strong Flour Used in Bread Production with Frozen Dough.

Abstract: We examined the properties of frozen dough made with an extra strong (ES) flour called Wildcat to determine the freezing resistance of the flour. The results were as follows: (1) Degradation of the frozen dough, which is evaluated as the decrease in specific loaf volume, was mostly induced by damage to the yeast from freezing. This damage lowers the gas retention of the dough, resulting in a weakness in its physical properties and reduction of its gassing power. (2) Properties of the ES flour as frozen dough w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Nevertheless, there are some limitations in the application of frozen dough. Yamauchi et al 11 found that frozen storage could cause damage to the gas-holding properties of the dough, while the production of glutathione by yeast during freezing could adversely affect the structure of the dough. Meziani et al 12 showed that freezing the dough at −30 and −40 °C led to dehydration of the dough network and the appearance of starch regrowth, which caused a decrease in elasticity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there are some limitations in the application of frozen dough. Yamauchi et al 11 found that frozen storage could cause damage to the gas-holding properties of the dough, while the production of glutathione by yeast during freezing could adversely affect the structure of the dough. Meziani et al 12 showed that freezing the dough at −30 and −40 °C led to dehydration of the dough network and the appearance of starch regrowth, which caused a decrease in elasticity.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, there are some limitations in the application of frozen dough. Yamauchi et al 11 . found that frozen storage could cause damage to the gas‐holding properties of the dough, while the production of glutathione by yeast during freezing could adversely affect the structure of the dough.…”
Section: Introductionmentioning
confidence: 99%